IMPLEMENTASI AKAD MUDHARABAH PADA PRODUK TABUNGAN HAJI - Dyah Ayu Paramitha; Diah Nurdiwaty (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2018)
The purpose of this research is (1) To know mudharabah mutlaqah contract implementation on Haji BRI Syariah Savings product at Bank BRI Syariah Branch of Kediri. (2) To find out the system and procedure of Tabungan Haji BRI Syariah iB product at Bank BRI Syariah Kediri Branch Office. (3) To find out what are the constraints of Tabungan Haji BRI Syariah iB products at Bank BRI Syariah Kediri Branch Office. The approach of this research uses descriptive qualitative research. The informant is an employee of Bank Syariah Branch Office of Kediri and the savings account of Haji BRI Syariah iB with data collection technique using documentation and interview. The conclusion of the research result is the product of Tabungan Haji BRI Syariah iB Kediri Branch Office using mudharabah mutlaqah contract and its enforcement is in accordance with the prevailing regulations. The system and procedures of the Savings Haji product of BRI Syariah iB are easy to apply, although there are still constraints from SISKOHAT which are sometimes offline.